Corporate Co-evolution in State-Dominant Business Networks: the Case of the Myanmar Port Authority - Kar, Ar (Curtin University, 2020)
This study aims to extend knowledge of corporate co-evolution by drawing on the development trajectories that have taken place among government-business networks in the state-dominant business environment of Myanmar. From the perspectives of co-evolution, upper echelons, and business network, and through qualitative inquiry, this study addresses why and how organisations co-evolve with their environment, how upper echelons with military backgrounds influence corporate co-evolution, and how a public authority co-evolves with private actors in the industry.